Re-examining the Brazilian South-Northeast labour income gap: A decomposition approach - Rodrigo Carvalho Oliveira; Raul da Mota Silveira Neto (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
The purpose of this article is to provide new evidence about the sources of regional income inequalities in Brazil along the wage distribution, taking into account the regional differentials in purchasing power. We use a unique and recent regional purchasing power index to adjust nominal values of the Brazilian metropolitan regions and consider recentred influence function (RIF) regressions to measure the contributions of different determinants of wages to the inequality between the S\~ao Paulo metropolitan region in the Southeast (the richest one, apart from Brasília) and each of the most important metropolitan regions of the Northeast (Fortaleza, Recife, and Salvador).
Keywords: C21; J31; J38; 330; Brazil; regional inequality; decomposition; wage distribution